2019
DOI: 10.1007/s40037-019-00531-w
|View full text |Cite
|
Sign up to set email alerts
|

Attrition among New Zealand medical students completing research degrees: A 20-year analysis

Abstract: IntroductionNot all medical students who intercalate research degrees go on to completion. No study to date has investigated the specific reasons. Understanding this minority would fill an important research gap.MethodsA list was obtained of intercalating medical students who enrolled at our institution between 1995 and 2014. Students who withdrew from an intercalated research degree were then invited to complete an online survey via email.ResultsOver the study period, 178 medical students commenced an interca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Previous studies found the dropout rate of medical students to range from 3.8% to 26% [ 24–31 ]. Some studies demonstrated a strong relationship between psychological problems (i.e., depression, burnout, anxiety, alcohol abuse) and the risk of dropout [ 30 , 32–34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies found the dropout rate of medical students to range from 3.8% to 26% [ 24–31 ]. Some studies demonstrated a strong relationship between psychological problems (i.e., depression, burnout, anxiety, alcohol abuse) and the risk of dropout [ 30 , 32–34 ].…”
Section: Introductionmentioning
confidence: 99%